Determinants and motivation factors in language learning - Jafarova Shabnam Shirvan (Modern Scientific Technology, 2025)
Motivation. Johnstone considers motivation as a stimulus to achieve a specific goal (Johnstone, 2000). Similarly, according to Ryan and Deci, being motivated means being in motion to develop or do something (McEown et.al., 2019). Crump believes that excitement, interest, desire, understanding, and enthusiasm for learning are the main components of motivation (Crump, 1995). The levels and types of motivation in any given individual are different from others. In other words, not only do individuals have different levels and amounts of motivation, but also different types of motivation. Cook concludes that language acquisition is not the same for all learners. Furthermore, it is suggested that there are three main factors that influence second language acquisition. These are age, personality, and motivation. The most important of these is motivation.